Anion exchange polymer, anion exchange membrane, method and device

By introducing high alkali resistance cationic groups and cationic side chains into the polyaryl polymer, the problem that anion exchange membrane is difficult to maintain alkali resistance while improving ion conductivity, achieving efficient and stable ion conduction and long-life membrane performance.

CN119529243APending Publication Date: 2025-02-28HUANENG YIMIN COAL POWER CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411693693.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

While improving the ion conductivity, existing anion exchange membranes are difficult to maintain alkali resistance stability, resulting in unstable operation in high temperature, high pressure and strong alkali environments and short life.

Method used

In the polyaryl polymer structure, cationic groups with high alkali resistance and cationic side chains that enhance ionic conductivity are introduced. By reasonably adjusting the value range of X and q, the reasonable distribution of cationic groups and side chains is ensured, and the alkali resistance stability and ionic conductivity of the polymer are improved.

Benefits of technology

It significantly enhances the alkali resistance and ion conductivity of the anion exchange membrane, can operate stably for a long time in a high pH environment, extends the service life of the device, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529243A_ABST
    Figure CN119529243A_ABST
Patent Text Reader

Abstract

According to the anion exchange polymer, the anion exchange membrane, the method and the device provided by the invention, a cationic group with high alkali resistance is introduced into a polyaryl polymer structure, and meanwhile, a cationic side chain is introduced, so that the ionic conductivity and the alkali-resistant stability of the anion exchange polymer are synchronously improved; the anion exchange membrane prepared from the anion exchange polymer has the advantages of excellent ionic conductivity and alkali-resistant stability, can stably operate for a long time in a high pH value environment, and is not easy to degrade or reduce the performance. Therefore, the anion exchange membrane has remarkable advantages in electrochemical processes such as water electrolysis hydrogen production, so that the anion exchange membrane has a wide application prospect in electrochemical devices such as a water electrolysis reactor and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion exchange polymers, and in particular to an anion exchange polymer, an anion exchange membrane, a method and a device. Background Art

[0002] As a powerful membrane material, anion exchange membrane plays a vital role in many electrochemical devices such as water electrolysis to produce hydrogen, alkaline fuel cells, flow batteries and electrodialyzers. Through their unique ability to selectively conduct anions, they enable ions to be efficiently and orderly transported in these devices, thus ensuring the stable operation and high performance of the equipment. The performance of anion exchange membranes directly determines the working efficiency and life of these electrochemical devices.

[0003] The performance evaluation of anion exchange membranes is mainly based on three key indicators: ion conductivity, chemical stability and mechanical strength. Ion conductivity is an important indicator to measure the ability of membrane materials to conduct ions, which is directly related to the transmission rate and efficiency of ions in electrochemical devices. Chemical stability determines whether the membrane material can maintain its original structure and performance under long-term operation and harsh environments. Mechanical strength is a key factor in whether the membrane material can withstand external pressure and deformation and maintain its integrity and service life. However, meeting these three performance indicators at the same time is undoubtedly a huge challenge for the research and development of anion exchange membranes.

[0004] Although many breakthroughs have been made in the research and development of anion exchange membranes in recent years, anion exchange membranes with excellent comprehensive performance are still relatively scarce. Especially in terms of ion conductivity and alkali stability, many existing anion exchange membranes are difficult to achieve an ideal balance. High ion conductivity usually means that the ion channels in the membrane material are more unobstructed, which is conducive to the rapid transmission of ions. However, this also often leads to a decrease in the alkali stability of the membrane material, because in an alkaline environment, high ion conductivity is often accompanied by the destruction of the ion channel structure and the degradation of the membrane material.

[0005] At present, although there are some advanced anion exchange membrane technologies that can improve the comprehensive performance of membrane materials to a certain extent, such as by introducing special chemical structural units or adopting new preparation processes, these technologies are still difficult to fully meet the high requirements for long-term operation stability in actual application scenarios such as electrolyzers. In practical applications, electrochemical devices such as electrolyzers need to operate for a long time and often face harsh environments such as high temperature, high pressure, and strong alkali. This requires that the anion exchange membrane must have extremely high chemical stability and mechanical strength to ensure that there will be no performance degradation and breakage during long-term operation. However, existing anion exchange membranes are often difficult to meet these requirements at the same time, resulting in unstable performance and short life in practical applications. Therefore, how to further improve the ion conductivity and alkali stability of anion exchange membranes is still an important direction of current research. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides an anion exchange polymer, anion exchange membrane, method and device, by introducing cationic groups with high alkali resistance into the polyaryl polymer structure, and simultaneously introducing cationic side chains, thereby simultaneously improving its ion conductivity and alkali resistance stability.

[0007] To achieve the above object, the present invention provides the following technical solution: an anion exchange polymer, the structural formula of the anion exchange polymer is as follows:

[0008] Wherein, A is an aromatic group; x is 50-99; and q is 0-10.

[0009] Furthermore, the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.

[0010] Furthermore, the value of X is 80-99.

[0011] The present invention also provides a method for preparing an anion exchange polymer, the specific steps of which are as follows: Dissolve 100 parts of an aromatic compound, x parts of 3-quinuclidinone hydrochloride or 3-quinuclidinone, and (100-x) parts of trifluoromethyl-p-(2-p-bromomethyl)phenethyl ketone in a solvent to obtain a mixture 1; At 0°C, a Lewis acid is added to the mixture 1, stirred for reaction, and then impurities are removed, washed, and dried to obtain an intermediate polymer; Dissolving 100 parts of the intermediate polymer and 100-1000 parts of quinuclidine in a solvent to obtain a cationic substituted polymer; The cationic substituted polymer is dissolved in a solvent, iodomethane is added under alkaline conditions for reaction, and the anion exchange polymer is obtained by precipitation, washing and drying.

[0012] Furthermore, the Lewis acid is trifluoromethanesulfonic acid and trifluoroacetic acid.

[0013] The present invention also provides an anion exchange membrane with high ion transport properties and alkali resistance stability, which is prepared by an anion exchange polymer. The structural formula of the anion exchange polymer is as follows:

[0014] Wherein, A is an aromatic group; x is 50-99; and q is 0-10.

[0015] Furthermore, the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene; and the value of X is 80-99.

[0016] Furthermore, the anion exchange polymer is dissolved in a solvent, poured into the groove of the flat glass plate, cross-linked in situ, and dried to form a film to obtain an anion exchange membrane.

[0017] The present invention provides an electrochemical device, in which the anion exchange membrane having high ion transport properties and alkali resistance stability is used.

[0018] The present invention provides a water electrolysis reactor, which adopts the anion exchange membrane with high ion transmission property and alkali resistance stability.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides an innovative anion exchange polymer, which cleverly introduces highly alkali-resistant cationic groups and cationic side chains that improve ion conductivity into the structure of polyaryl polymers. Specifically, in the structural formula of the polymer, A represents an aromatic group, and the selection of these aromatic groups provides a stable skeleton structure for the polymer. The value range of x is between 50 and 99, which ensures the reasonable distribution of cationic groups and side chains in the polymer; the value range of q is between 0 and 10, which further regulates the performance of the polymer. This design not only significantly enhances the alkali resistance stability of the polymer, but also greatly improves its ion transport performance.

[0020] By using the above-mentioned innovative anion exchange polymer, the present invention successfully prepares an anion exchange membrane with high ion transport properties and alkali resistance stability. During the preparation process, the anion exchange polymer is first dissolved in a solvent, and then poured into the groove of a flat glass plate to form a stable membrane structure through an in-situ cross-linking technology. Finally, after drying, an anion exchange membrane with excellent performance can be obtained. The advantages of this membrane are its excellent ion conductivity and alkali resistance stability, which can operate stably for a long time in a high pH environment and is not prone to degradation or performance degradation. This makes it have significant advantages in electrochemical processes such as electrolysis of water to produce hydrogen, so the anion exchange membrane of the present invention has broad application prospects in electrochemical devices such as electrolysis of water reactors.

[0021] The anion exchange membrane provided by the present invention has high ion conductivity, can significantly improve the efficiency of the electrochemical process, reduce energy consumption, and has strong alkali resistance and stability, can operate stably for a long time in a harsh alkaline environment, and prolong the service life of the device. In addition, the preparation method of the present invention is simple and efficient, reduces production costs, makes the commercial application of electrochemical devices and water electrolysis reactors more feasible, and provides strong technical support for the development of the new energy industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The ionic conductivity data of the anion exchange membrane prepared by the present invention at 80°C; Figure 2 A data graph showing the ion conductivity retention rate of the anion exchange membrane prepared by the present invention after 2000 hours of alkali immersion. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0024] The present invention provides an anion exchange polymer with high ion transport properties and alkali resistance stability. The anion exchange polymer introduces a cationic group with high alkali resistance and a cationic side chain for improving ion conductivity into a polyaryl polymer structure. The specific structure is as follows:

[0025] Wherein, A is an aromatic group, and the aromatic group can be one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene; the value of x is 50-99, preferably 80-99; the value of q is 0-10.

[0026] The anion exchange polymer can be used to prepare an anion exchange membrane with excellent ion conductivity and alkali resistance stability. The specific preparation steps are as follows: 1) Preparation of anion exchange polymers; Step 1, dissolving 100 parts of an aromatic compound, x parts of 3-quinuclidinone hydrochloride or 3-quinuclidinone, and (100-x) parts of trifluoromethyl-p-(2-p-bromomethyl)phenethyl ketone in a solvent to obtain a mixture 1; Step 2: adding Lewis acid to mixture 1 at 0°C, stirring to react to obtain a viscous purple product, removing impurities, washing, and drying to obtain an intermediate polymer; Step 3, dissolving 100 parts of the intermediate polymer and 100-1000 parts of quinuclidine in a solvent to obtain a cation-substituted polymer; Step 4: dissolving the cationic substituted polymer in a solvent, adding iodomethane under alkaline conditions to react, precipitating, washing, and drying to obtain an anion exchange polymer, wherein the anion exchange polymer is an anion of I - Functionalized polymers; 2) Anion exchange membrane preparation The anion exchange polymer is dissolved in a solvent and poured into the groove of a flat glass plate to form a cross-linked network structure in situ, and then dried to form a film to obtain an anion exchange membrane.

[0027] Example 1: A is p-terphenyl, x=80, q=0 A method for preparing an anion exchange membrane with high ion transport properties and alkali resistance stability is as follows: (1) Weigh 10.0 mmol of p-terphenyl into a 100 mL three-necked flask, add 8.0 mmol of 3-quinuclidine hydrochloride and 2.0 mmol of trifluoromethyl p-(p-bromomethyl)phenethyl ketone, and add 10 mL of dichloromethane to dissolve the reactants. Add 12 mL of trifluoromethanesulfonic acid and 1 mL of trifluoroacetic acid at 0 °C, and stir mechanically for 12 hours. Pour the viscous purple product into 1M K2CO3 solution, soak at room temperature for 24 hours, filter to obtain a white solid product, wash it thoroughly with deionized water, and dry it to obtain an intermediate polymer;

[0028] (2) Weigh 1.2 g of the intermediate polymer and 1.1 g (10 mmol) of quinuclidine and dissolve them in 10 mL of chloroform. Stir at room temperature for 12 h to obtain a cation-substituted polymer.

[0029]

[0030] (3) Weigh 1.2 g of the above cationic substituted polymer into a 100 mL single-necked flask, add 15 mL of dimethyl sulfoxide, and add 150 μL of trifluoroacetic acid to promote the dissolution of the polymer. After the polymer is completely dissolved, add 0.36 g of potassium carbonate and 300 μL of iodomethane, and react at room temperature for 24 h. Pour the reaction product into ethyl acetate to precipitate a yellow precipitate, wash it with ethyl acetate several times, then wash it with water and dry it, and obtain an anion of I - of functionalized polymers.

[0031] (4) Weigh 1g of the functionalized polymer, add 50mL of dimethyl sulfoxide, and pour it into the groove of a flat glass plate after it is fully dissolved. Dry it at 80°C for 48 hours to form a film, and at the same time, form a cross-linked network structure in situ. After the film is peeled off the glass plate, it is immersed in a 1M KOH solution and ion exchange is performed at room temperature for 48 hours to obtain an anion of OH - The anion exchange membrane has the following specific structural formula:

[0032] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 193 mS / cm at 80°C; Figure 2 As shown in the figure, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali immersion for 2000 hours is 97.1%. The introduction of cationic side chains enables the anion exchange membrane to have extremely high ion conductivity while maintaining excellent alkali resistance and stability.

[0033] Example 2: A is p-terphenyl, x=50, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the specific structural formula is as follows: .

[0034] Example 3: A is p-terphenyl, x=99, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the specific structural formula is as follows: .

[0035] Example 4: A is p-terphenyl, x=80, q=2 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the specific structural formula is as follows: .

[0036] Example 5: A is p-terphenyl, x=80, q=10 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the specific structural formula is as follows: .

[0037] Example 6: A is biphenyl, x=80, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the specific structural formula is as follows: .

[0038] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 198 mS / cm at 80°C; Figure 2 As shown in the figure, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali immersion for 2000 hours is 95.2%. The introduction of cationic side chains enables the anion exchange membrane to have extremely high ion conductivity while maintaining excellent alkali resistance and stability.

[0039] Example 7: A is 80% p-terphenyl + 20% m-terphenyl, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane, and the specific structural formula is as follows: .

[0040] Example 8: A is 80% p-terphenyl + 20% diphenylethane, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane, and the specific structural formula is as follows: .

[0041] Example 9: A is 90% p-terphenyl + 10% 9,9-dimethylfluorene, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane, and the specific structural formula is as follows: .

[0042] Comparative Example 1: In Example 1, step (3) is not performed, and trifluoromethyl-p-(2-p-bromomethyl)phenethyl ketone is replaced with trifluoroacetophenone to obtain an anion exchange membrane having the following structural formula:

[0043] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity, such as Figure 1 As shown, the anion exchange membrane obtained in this comparative example has an ionic conductivity of 170 mS / cm at 80°C; Figure 2 As shown in FIG. 1 , the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali leaching for 2000 hours was 97.5%. Compared with Example 1, Comparative Example 1 does not contain a cationic side chain, and its alkali resistance stability is relatively close to that of Example 1 (see FIG. 1 ). Figure 2 ), but its ionic conductivity is significantly lower than that of Example 1 (see Figure 1 ), indicating that the introduction of cationic side chains enables the anion exchange membrane to have extremely high ionic conductivity while maintaining excellent alkali resistance and stability.

Claims

1. An anion exchange polymer, characterized in that The structural formula of the anion exchange polymer is as follows: Wherein, A is an aromatic group; x is 50-99; and q is 0-10.

2. An anion exchange polymer according to claim 1, characterized in that The aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.

3. An anion exchange polymer according to claim 1, characterized in that The value of X is 80-99.

4. The method for preparing an anion exchange polymer according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: Dissolve 100 parts of an aromatic compound, x parts of 3-quinuclidinone hydrochloride or 3-quinuclidinone, and (100-x) parts of trifluoromethyl-p-(2-p-bromomethyl)phenethyl ketone in a solvent to obtain a mixture 1; At 0°C, a Lewis acid is added to the mixture 1, stirred for reaction, and then impurities are removed, washed, and dried to obtain an intermediate polymer; Dissolving 100 parts of the intermediate polymer and 100-1000 parts of quinuclidine in a solvent to obtain a cationic substituted polymer; The cationic substituted polymer is dissolved in a solvent, iodomethane is added under alkaline conditions for reaction, and the anion exchange polymer is obtained by precipitation, washing and drying.

5. The method for preparing an anion exchange polymer according to claim 4, characterized in that: The Lewis acids are trifluoromethanesulfonic acid and trifluoroacetic acid.

6. An anion exchange membrane having high ion transport properties and alkali resistance stability, characterized in that: It is prepared by using anion exchange polymer, and the structural formula of the anion exchange polymer is as follows: Wherein, A is an aromatic group; x is 50-99; and q is 0-10.

7. An anion exchange membrane having high ion transport properties and alkali resistance stability according to claim 6, characterized in that: The aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene; and the value of X is 80-99.

8. An anion exchange membrane with high ion transport properties and alkali resistance stability according to claim 6, characterized in that: The anion exchange polymer is dissolved in a solvent, poured into the groove of a flat glass plate, cross-linked in situ, and dried to form a film to obtain an anion exchange membrane.

9. An electrochemical device, characterized in that: The anion exchange membrane having high ion transport properties and alkaline stability as described in any one of claims 6 to 8 is used.

10. A water electrolysis reactor, characterized in that: An anion exchange membrane having high ion transport properties and alkali resistance stability as described in any one of claims 6 to 8 is used.

Citation Information

Cited By

  • Aromatic quinine onium side chain functionalized quinine-aromatic copolymer and preparation method thereof

    CN121108434A

  • Preparation method of copolymerization type anionic membrane material

    CN121554679A

  • Method for preparing copolymeric anionic membrane material

    CN121554679B